Analysis of the influence of pavement irregularities on the lifespan of a vehicle's drive-wheel half shaft - Simović, Sreten (Strojniški vestnik, 2016)
As a complex technical system, a vehicle requires a full analysis of its dynamic behaviour. A vehicle is the research subject requiring a detailed analysis of all separate systems both individually and in mutual interaction. One of the technical aspects of vehicle analysis is the lifespan of each element. This paper presents an analysis of the impact of the characteristics of pavement irregularities on the lifespan of a half shaft. In this paper, a mathematical model and a computer simulation of vehicle half-shaft loads have been set up. The importance of this approach is reflected in the use of state-of-the-art computational methods of analysis. The obtained results enable the drawing of clear conclusions about the effects of pavement properties on the lifespan of a vehicle half shaft.
Keywords: nepravilnosti; obremenitve; polgredi; vozila; vozišče; vzmetenje; življenjska doba